Software Architecture in Practice, 4th Edition - Bass, Len; Clements, Paul; Kazman, Rick (Addison-Wesley Professional, 2021)
The Definitive, Practical, Proven Guide to Architecting Modern Software--Now Fully Updated Now with nine new chapters, Software Architecture in Practice, Fourth Edition, thoroughly explains what software architecture is, why it's important, and how to design, instantiate, analyze, evolve, and manage it in disciplined and effective ways. Three renowned software architects cover the entire lifecycle, presenting practical guidance, expert methods, and tested models for use in any project, no matter how complex. You'll learn how to use architecture to address accelerating growth in requirements, system size, and abstraction, and to manage emergent quality attributes as systems are dynamically combined in new ways. With insights for utilizing architecture to optimize key quality attributes--including performance, modifiability, security, availability, interoperability, testability, usability, deployability, and more--this guide explains how to manage and refine existing architectures, transform them to solve new problems, and build reusable architectures that become strategic business assets. Discover how architecture influences (and is influenced by) technical environments, project lifecycles, business profiles, and your own practices Leverage proven patterns, interfaces, and practices for optimizing quality through architecture Architect for mobility, the cloud, machine learning, and quantum computing Design for increasingly crucial attributes such as energy efficiency and safety Scale systems by discovering architecturally significant influences, using DevOps and deployment pipelines, and managing architecture debt Understand architecture's role in the organization, so you can deliver more value.
Online resource; Title from title page (viewed July 27, 2021)